Ultrastable Fe–N–C Fuel Cell Electrocatalysts by Eliminating Non‐Coordinating Nitrogen and Regulating Coordination Structures at High Temperatures. Issue 5 (18th December 2022) - Xia, Dongsheng; Tang, Xuan; Dai, Sheng; Ge, Rile; Rykov, Alexander; Wang, Junhu; Huang, Tzu‐Hsi; Wang, Kuan‐Wen; Wei, Yinping; Zhang, Kai; Li, Jia; Gan, Lin; et al.
Abstract: Pyrolyzed Fe–N–C materials have attracted considerable interest as one of the most active noble‐metal‐free electrocatalysts for the oxygen reduction reaction (ORR) in proton exchange membrane fuel cells (PEMFCs). Despite significant progress is made in improving their catalytic activity during past decades, the Fe–N–C catalysts still suffer from fairly poor electrochemical and storage stability, which greatly hurdles their practical application. Here, an effective strategy is developed to greatly improve their catalytic stability in PEMFCs and storage stability by virtue of previously unexplored high‐temperature synthetic chemistry between 1100 and 1200 °C. Pyrolysis at this rarely adopted temperature range not only enables the elimination of less active nitrogen‐doped carbon sites that generate detrimental peroxide byproduct but also regulates the coordination structure of Fe–N–C from less stable D1 (O–FeN4 C12 ) to a more stable D2 structure (FeN4 C10 ). The optimized Fe–N–C catalyst exhibits excellent stability in PEMFCs (>80% performance retention after 30 h under H2 /O2 condition) and no activity loss after 35 day storage while maintaining a competitive ORR activity and PEMFC performance. Abstract : An ultrastable Fe–N–C electrocatalyst for the oxygen electroreduction in proton exchange membrane fuel cells is developed by virtue of high‐temperature pyrolysis chemistry at above 1100 °C, which enables the regulation of atomic coordination structures of Fe centers and the elimination of non‐coordinating nitrogen dopants producing detrimental peroxide byproduct.